Tsunami loads and effects : guide to the tsunami design provisions of ASCE 7-16 - Robertson, Ian N. (ASCE Press, 2020)
The devastating tsunamis that struck Chile and Japan in 2010 and 2011 underscored the critical need for new structural design criteria to improve building resilience and safeguard human life. They also provided a wealth of information that could form the basis for estimating tsunami loads and effects and guiding the development of a design methodology. A team of researchers and practitioners took up the challenge, which resulted in the inclusion of provisions for tsunami loads in Standard ASCE/SEI 7-16, Minimum Design Loads and Associated Criteria for Buildings and Other Structures.For many US structural and geotechnical engineers, ASCE 7-16's provisions and commentary will be their first exposure to tsunami design. In this companion guide, author Ian Robertson helps engineers and allied professionals understand the background and development of the new provisions. He guides them through the application of tsunami design with a series of clear and detailed examples based on prototypical buildings. He connects the ASCE 7-16 tsunami provisions to prior design guidelines, laboratory research, and field surveys. In addition, he explains the key concepts in the provisions, including tsunami risk categories; inundation depth and flow velocities; structural design procedures; and hydrostatic, hydrodynamic, and debris impact loads. Robertson demonstrates the application of these concepts in numerous examples and a full-length tsunami design of a prototype building. The guide also explains the tsunami provisions for foundation design, structural countermeasures, vertical evacuation refuges, nonstructural components and systems, and critical nonbuilding structures.Tsunami Loads and Effects: Guide to the Tsunami Design Provisions of ASCE 7-16 is a clear and authoritative explanation of the tsunami load requirements that will be welcomed by structural, coastal, and geotechnical engineers, as well as architects, building code officials, contractors, and emergency managers.
Keywords: Tsunami resistant design -- Standards -- United States -- Prevention.; Tsunami damage -- Prevention.; Ocean waves.; Wave resistance (Hydrodynamics); elektronické knihy; electronic books